Chemical characteristics of surface and phreatic water and their effects on the growth of Populus euphartica Oliv. in desert areas of Tarim National Nature Reserve, China (Bangladesh Journal of Botany, 2021)
Chemical characteristics of surface water and phreatic water and their relationship with the growth of Populus euphratica Oliv. were explored. In the study area, hydrochemical types of the surface water were mainly SCaⅢ or ClNaⅢ (Based on the O. A. Arliekin's classification) and PH value of the surface water was below 8.0. The surface water from various sampling sites has a higher total hardness belonging to hard water and extremely hard water. The contents of sulfates and chlorides in the surface water in the protection zone ranged from 204.1 to 486.3 mg/l and from 70.9 to 239.9 mg/l, respectively. Phreatic water is mainly recharged by the surface water infiltration. In terms of water quality, TDS, total hardness and total alkalinity of phreatic water at W2 sampling point were 17.3, 9.3 and 4.7 times of surface water, respectively. Populus euphratica was able to grow normally in the environment of brackish water, where total hardness, total alkalinity, and TDS of overflowing river were in the range of 325.3~769.5, 142.6~290.3 and 782.2~1037.5 mg/l, respectively. The Populus euphratica in juvenile phase was a few, and its rejuvenation was confronted with difficulty. The present study can provide a reference for exploring the water quality characteristics of surface and phreatic water and their relationship with the growth of Populus euphratica.Bangladesh J. Bot. 50(3): 831-836, 2021 (September) Special